PERILAKU PETANI SAWAH DALAM PENANGANAN PESTISIDA DI DESA WAIMITAL, SERAM BAGIAN BARAT - Dhia Tiara Ayu; Jusmy. D Putuhena; Debby. V Pattimahu (JURNAL HUTAN PULAU-PULAU KECIL, 2023)
Abstract This study aims to determine the types of pesticides used and the behavior of farmers towards the use of pesticides in Waimital, west Seram. This research uses a survey method with interview techniques, in which there are stages such as interviews using a list of questions, observations to households and the environment around where they live, and interviews with informants such as agricultural extension workers and farmer contacts. The results of this study indicate that the types of pesticides used are insecticides, herbicides, and fungicides. In addition, the behavior of farmers in the use of pesticides is classified as good with a total score 2973 and average score of 59,46.